2020
DOI: 10.3390/cells9061419
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Derived LINC00960 and LINC02470 Promote the Epithelial-Mesenchymal Transition and Aggressiveness of Bladder Cancer Cells

Abstract: Exosomes are essential for several tumor progression-related processes, including the epithelial–mesenchymal transition (EMT). Long non-coding RNAs (lncRNAs) comprise a major group of exosomal components and regulate the neoplastic development of several cancer types; however, the progressive role of exosomal lncRNAs in bladder cancer have rarely been addressed. In this study, we identified two potential aggressiveness-promoting exosomal lncRNAs, LINC00960 and LINC02470. Exosomes derived from high-grade bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 57 publications
(72 reference statements)
1
36
0
Order By: Relevance
“…Reportedly, LINC00960 expression is up-regulated in the fibroblasts of idiopathic pulmonary fibrosis, and LINC00960 negatively regulates its proliferation [25]. A recent study reports that, through up-regulating βcatenin signal, Notch signal, and Smad2/3 signal, exosome-derived LINC00960 can promote the malignant behaviors of low-grade bladder cancer cells and induce epithelial-mesenchymal transition, thus working as a potential liquid biomarker to monitor the progression of bladder cancer [26]. This study found that LINC00960 expression was up-regulated in PDAC, which is consistent with the previous report [16].…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, LINC00960 expression is up-regulated in the fibroblasts of idiopathic pulmonary fibrosis, and LINC00960 negatively regulates its proliferation [25]. A recent study reports that, through up-regulating βcatenin signal, Notch signal, and Smad2/3 signal, exosome-derived LINC00960 can promote the malignant behaviors of low-grade bladder cancer cells and induce epithelial-mesenchymal transition, thus working as a potential liquid biomarker to monitor the progression of bladder cancer [26]. This study found that LINC00960 expression was up-regulated in PDAC, which is consistent with the previous report [16].…”
Section: Discussionmentioning
confidence: 99%
“…pointed out that exosomal lnc_00960 and lnc_02470 promoted EMT and the aggressiveness of BCa cells. They treated BCa TSGH-8301 cells with exosomes derived from BCa T24 or J82 cells, leading to decreased E-cadherin levels and increased N-cadherin, vimentin, MMP2, and MMP9 levels in TSGH-8301 cells ( 66 ). Berrondo et al.…”
Section: The Biological Roles Of Exosome-derived Ncrnas In Bcamentioning
confidence: 99%
“…Exosomes are vesicles of endocytic origin and continuously released from the bladder [91], which can mediate communication between cells through the transfer of nucleic acids [92][93][94][95] and proteins [96] in BC. Numerous studies have been conducted to investigate the role of exosomes in patients with BC.…”
Section: Circulating Mirnas and Othersmentioning
confidence: 99%